Optimal Operational and Economical Coordination Strategy for a Smart Neighborhood - Paterakis, Nikolaos G.; Pappi, Iliana N.; Catalao, Joao P. S.; Erdinc, Ozan (IEEE, 2015)
The introduction of smart end-users is a vital point towards the smart grid vision. In this respect, smart households have drawn significant attention recently. Home energy management systems (HEMS) in smart households and transformer energy management units have different objectives that can sometimes be conflicting. Thus, a novel interactive optimum operating strategy that considers all possible aspects in each smart household together with internal bi-directional power flows within the household structure from economic (minimization of household daily electricity usage costs) and technical (avoidance of transformer overloading) perspective is proposed in this study. To the best knowledge of the authors, this is the first study in the literature combining all of the possible operational possibilities in HEMS of smart households together with internal household bi-directional power flows and the technical limitations of a transformer unit serving a neighborhood of smart households under a mixed-integer linear programming (MILP) framework.
Keywords: Distributed generation; home energy management system; electric vehicles; smart neighborhood; ENERGY MANAGEMENT; DEMAND RESPONSE; TRANSFORMER; SYSTEM; IMPACT; Engineering